Organizational and institutional factors affecting high-speed rail safety in Japan. (August 2020) - Bugalia, Nikhil; Maemura, Yu; Ozawa, Kazumasa
Highlights: In ultra-safe systems, gradual deterioration of information creates safety issue. Excessive reliance on "Learning from the past" may also lead to accidents. The regulatory safety protection may become ineffective for self-regulated systems. System-thinking based risk-assessment by both operator and regulator is necessary. Leading indicators for organizational components should help improve system-safety. Abstract: The Japanese High-Speed Railway (HSR), is renowned for its impeccable safety record of zero passenger fatalities. However, a limited academic discussion has taken place on the organizational and institutional factors affecting HSR safety in Japan, as opposed to technological solutions. A recent series of HSR accidents in Japan have also warranted attention on organizational and institutional factors affecting HSR safety. The objective of the present study is to utilize systems approach to highlight the current organizational and institutional safety issues within Japanese HSR, and to provide a discussion on improving current practices. First, the study develops a taxonomy of accident causes in Japanese HSR, using previously unanalyzed official accident reports available only in Japanese. The taxonomy analysis reveals common accident causal factors, including the failure to sense degradation in procedures, and the failure to establish knowledge-based on thorough risk assessments. The paper then presents an in-depth analysis of the only "Serious Accident" in Japanese HSR. Information on the serious accident obtained through official accident reports and expert interviews is combined using a System-Theoretic Accident Model and Process (STAMP) analysis, which reveal a new accident archetype at the organizational and institutional level. The archetype demonstrates the common failure causes for the operator and the regulator, thereby making their apparent redundancy ineffective. The archetype is helpful in identifying theoretical improvements in current safety practices. The study also concludes that the adoption of a systematic risk-assessment approach is necessary to enable proactive safety management in complex ultra-safe systems like the Japanese HSR.